Competitive Priorities as Operations Management Strategy Enablers - Muhammad Masyhuri (International Journal of Management Science and Application, 2023)
This paper discusses the importance of applying competitive priorities that include cost, quality, time, and flexibility as the basis for a company’s operating strategy. Some examples of successful companies applying these types of competitive priorities will be explained. However, there is no specific recipe that companies should follow in choosing the right competitive priorities, as each individual company has a different competitive strategy and resource approach. In fact, there is no guarantee that selecting specific competitive priorities will maintain the company’s position in the marketplace, because selection requires a critical and continuous process across the company's conditions. In a dynamic business environment, companies should focus on strategic flexibility and innovation capabilities as additional tools to current competitive priorities. Finally, the role of the company’s management is crucial, as it can carefully define the objectives of the competitive priorities and the improvement of the applied innovation strategy.